Relative hand grip strength and functional fitness among older adults with type II diabetes in Egypt: A cross-sectional study - Youssef Elhamrawy, Mohammed; Hassan, Ali Mohammed; George, Jobby; Zaher Basha, Sami Ahmed; Mohammed Sarhan, Mohammed Ali; Abdelrehim, Zeinab M; Said, Mohamed T.; Elgayar, Saher Lotfy (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Population aging, diabetes, and insufficient physical activity have become pressing public health issues in Egypt. Addressing these challenges can enhance the quality of life for the aging population and reduce the overall public health burden. This study recruited 200 participants, divided into two groups: individuals with type 2 diabetes mellitus (T2DM) and healthy non-diabetic controls. Participants were assessed for relative handgrip strength (rHGS) using a hand dynamometer, and for functional fitness using the Timed Up and Go test (TUG), the 30-second chair stand, and the 2-minute walk test (2-MWT), all during the same visit. The mean relative hand grip strength (rHGS) and the functional assessment (TUG, 30-second chair stands and 2-MWT) were significantly lower in the diabetic group compared to the group with no diabetes (p<0.05). Both rHGS and functional level are significantly lower in elderly diabetics as compared with healthy elderly subjects in Egypt (p<0.05). Also, among the Egyptians, rHGS and functional level in elderly participants with type 2 diabetes are strongly correlated with their glycemic control (p<0.05). The study highlights the importance of monitoring physical function as part of diabetes management in older adults.